MANAGEMENT OF EDUCATIONAL FACILITIES AND INFRASTRUCTURE IN HIGH SCHOOL SCHOOLS IN MERAUKE REGENCY - Datu, Agusthina; Prasojo, Lantip Diat (PT. Jurnal Center Indonesia Publisher, 2025)
This study aims to determine (1) the management of educational facilities and infrastructure in senior high schools throughout Merauke Regency. (2) Identify factors supporting the management of educational facilities and infrastructure in senior high schools throughout Merauke Regency. (3) Identify factors inhibiting the management of educational facilities and infrastructure in senior high schools throughout Merauke Regency. This study is a qualitative study. Data collection techniques used observation, interviews, and documentation. Data validity was verified using source triangulation and technical triangulation. Data analysis included data condensation, data presentation, and conclusion drawing. The results of this study show that (1) management of educational facilities and infrastructure in high schools throughout Merauke Regency has been carried out. This has been done in SMAN 1 Merauke, SMAN 2 Merauke and KPG Khas Papua Merauke. This is done by managing BOS funds, managing facilities and infrastructure such as providing fans in each class and conducting workshops for teachers to improve their abilities in the teaching process and the quality of education. Supporting factors for management of educational facilities and infrastructure in high schools throughout Merauke Regency such as in SMAN 1 Merauke, namely the principal has a high commitment to managing and prioritizing infrastructure, in SMAN 2 Merauke such as recruiting competent teachers in their fields, in KPG Khas Papua Merauke such as the commitment of solid leadership & team, collaborative culture. Inhibiting factors for the management of facilities and infrastructure in improving the quality of education in high schools throughout Merauke Regency, such as at SMAN 1 Merauke, are many old and damaged infrastructure, at SMAN 2 Merauke, such as disagreements regarding the policies made, at KPG Khas Papua Merauke, such as budget limitations & price/logistics fluctuations.